Larrissy, Edward. W.B. Yeats – Irish Writers in Their Time - Annunciação, Viviane Carvalho da (ABEI Journal, 2011)
Larrissy, Edward. W.B. Yeats – Irish Writers in Their Time. Dublin & Oregon: Irish Academic Press, 2010.